Brand Ambassador and the Effect to Consumer Decision on Online Marketplace in Indonesia - Eko Mohammad Fitrianto; Nofiawaty Nofiawaty; Iisnawati Iisnawati (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
This research purpose is to examine the effect of brand ambassador to consumer decision using the VisCAP indicator (Visual, Credibility, Attraction, and Power aspect). Using a descriptive design with a single cross-sectional. The samples were taken from 203 people, who had watched the advertisement and had visited the online market. The object of research is an Indonesian young famous singer, Isyana Sarasvati, who become a brand ambassador of Tokopedia (one of the largest online store in Indonesia). Regarding VisCAP indicators are used to measure the brand ambassador’s performance, Credibility is an important thing that influences purchase intention from the brand ambassador of Tokopedia, while the others are insignificant. Brand Ambassador produces differences in variables that influence purchase intention. The marketplace could use ambassador to influence consumer decisions, but they have to realize that every ambassador has different characters and variables that could influence consumer decisions. This paper offers originality such as Indicators on VisCAP that influence purchase intention on Indonesia people could be different on each of the ambassadors. And this paper proposes a future research ide such as develop new research by using transfer meaning approach that could analyze whether the values possessed by ambassadors can spread to products and accepted by consumers